THE EFFECT OF TEMPERATURE ON THE ENGINEERING PROPERTIES CONSOLIDATION BEHAVIORS OF SOFT SOIL - Rusdiansyah; Markawie (Journal of Applied Engineering Science, 2021)
Research on soil behavior due to changes in heat temperature in the soil mass is still relatively small. Even though, the phenomenon of increasing temperature in the soil mass is frequently occured. For example, there is an increase in temperature in the ground besides the problem of heat propagation under the road due to land fires, as well as the presence of waste heat from nuclear power plant in the soil medium, the operation of electric cables in the ground which causes heat, and the gas pipelines and oil pipes embedded in the ground, which generates heat around it, as well as thermal energy storage that are embedded in the soil.This research was conducted to get answers to how the behavior of the curve of the clay soft soil consolidation is due to changes in temperature. Mainly to get knowledge about the effect of temperature on changes in the value of mechanical parameters of soil consolidation, such as clay soft soil compression index (Cc), swelling index (Cs), volume change coefficient (mv), coefficient of consolidation (Cv), and hydraulic conductivity (k) of clay soft soil. In conducting the research, the material used was clay soft soil in undisturbed condition originating from a swampland locating in South Kalimantan, Indonesia, while the main tool used was a modified consolidation test device by adding an artificial heating device whose temperature could be adjusted with a temperature control device and temperature sensor. The temperatures applied to the test specimens were 40oC, 60oC 75oC, and 85oC.The results showed that changes in temperature in the soil could affect the compressibility of the soil, where the higher the temperature (heat) of the soil, the greater the soil compressibility. The increase in temperature in the soil causes an increase in the value of soil compressibility parameters such as the soil compression index (Cc), the coefficient of consolidation (Cv), and the swelling index (Cs). The value of compression index (Cc) of clay soft soils has a greater increase than the increase in other compressibility parameters when the temperature of clay soft soil increases (hot). In addition, the presence of high soil temperatures (hot conditions) in the soil can reduce changes in soil volume, where the volume change coefficient (mv) of clay soft soil tends to decrease if the soil temperature increases. Changes in soil temperature also affect soil permeability, where the seepage properties of clay soft soil tend to increase along with an increase in temperature in the soil.
Keywords: Temperature, consolidation test, soil compression behavior, clay soft soil.